Pengembangan Wisata Vulkan Merapi - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
ABSTRACT: Merapi volcano is one of the most active and famous volcano in the world. It's has been oriented to be developed as a nature based tourism resort. Part of ecotravelers visit Yogyakarta for climbing the top of the volcan and seeing the beautiful landscape of Merapi. Moreover, there is a. tend to realize Merapf as a special interesttourism object. Basically, Merapi Volcano created a specific villages. The ecosystem of Merapi such asgeosystem, and sociosystem can be became tourism object. In the future, Merapi will be one of the global tourism natural heritage. During the eruption period, the visitor could seen the beauty of pyroclastic flow from several observation stations or points of view to enrich the night attraction in Yogyakarta.